2005
DOI: 10.1017/s1041610205001584
|View full text |Cite
|
Sign up to set email alerts
|

Effect of morning bright light treatment for rest–activity disruption in institutionalized patients with severe Alzheimer's disease

Abstract: Although significant improvements were found in subjects with aberrant timing of their rest-activity rhythm, morning bright light exposure did not induce an overall improvement in measures of sleep or the rest-activity in all treated as compared to control subjects. The results indicate that only subjects with the most impaired rest-activity rhythm respond significantly and positively to a brief (one hour) light intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
118
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(135 citation statements)
references
References 26 publications
5
118
0
Order By: Relevance
“…If aging reduces visual inputs to the pineal gland or SCN, bright-light therapy might also rescue the disruption of circadian rhythm. Indeed, bright-light treatment improves circadian rhythms or sleep-wake cycles in both SAMP8 and humans with Alzheimer's disease (Dowling et al 2005;Miyamoto et al 1998;Yamadera et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…If aging reduces visual inputs to the pineal gland or SCN, bright-light therapy might also rescue the disruption of circadian rhythm. Indeed, bright-light treatment improves circadian rhythms or sleep-wake cycles in both SAMP8 and humans with Alzheimer's disease (Dowling et al 2005;Miyamoto et al 1998;Yamadera et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Even in severe dementia morning light therapy might lead to phase advances of circadian rhythms and improve behavioral symptoms (75), and both morning and evening light therapy improves circadian parameters and leads to consolidation of sleep (74). Dowling et al (76) did not report beneficial effects of light therapy on sleep parameters in institutionalized AD patients, but the light therapy did lead to a more stable circadian phase, and it has been suggested that those AD patients with the most severe circadian abnormality are most likely to respond to light therapy (77). Efficacy of light therapy might also be enhanced significantly in combination with melatonin treatment (78).…”
Section: Chronotherapeutics In Admentioning
confidence: 99%
“…It is known that with the progression of neurodegenerative dementias, sleep is disrupted; therefore maintaining the sleep/wake cycle is a biologically plausible intervention. The variation in the intensity of light used across studies as well as the timing were critical to the outcomes observed (Dowling 2005), and likely account for the differences in study results.…”
Section: Light Therapymentioning
confidence: 99%